A rare case of spinal hydatid cyst (echinococcosis) presenting with paraparesis - Rathi, Tejas D.; Borlepowar, Pooja; Sawadh, Ritesh; Atkar , Chandrshekhar M. (International Journal of Research in Medical Sciences, 2023)
Spinal hydatid cysts, although rare, can lead to debilitating neurological deficits if not promptly diagnosed and managed. We present an intriguing case of a 60-year-old male who presented with sudden-onset paraplegia, an unusual manifestation of spinal hydatid disease. The clinical complexity of paraplegia prompted a comprehensive diagnostic journey involving clinical, and radiological evaluations. Imaging studies unveiled a large hydatid cyst within the spinal canal, with epidural extension compressing the spinal cord. Surgical intervention was undertaken, and the cyst was successfully excised, leading to partial neurological recovery. This case serves as a reminder of the diverse clinical presentations of hydatid cysts and highlights the significance of maintaining a high index of suspicion in endemic regions. Early diagnosis, tailored management, and heightened awareness are pivotal in averting irreversible neurological damage and enhancing patient outcomes in such challenging cases.